My man Jeeves - Wodehouse, P. G. (Pelham Grenville), 1881-1975 (Salt Lake City, UT : Project Gutenberg, 2005)
"My Man Jeeves" by P. G. Wodehouse is a collection of short stories first published in May 1919. The eight stories split between two worlds: half introduce the now-legendary duo of gentleman Bertie Wooster and his ingenious valet Jeeves, while the others feature Reggie Pepper, an early prototype for Bertie. These tales of comic misadventures, romantic entanglements, and clever solutions established characters who would become enduring icons of English humor. (This is an automatically generated summary.)
Leave it to Jeeves -- Jeeves and the unbidden guest -- Jeeves and the hard-boiled egg -- Absent treatment -- Helping Freddie -- Rallying round old George -- Doing Clarence a bit of good -- The aunt and the sluggard.
Wikipedia page about this book: https://en.wikipedia.org/wiki/My_Man_Jeeves
Release date is 2005-05-01
Suzanne L. Shell, Charles Franks and the Online Distributed Proofreading Team
Keywords: Humorous stories; England -- Fiction; Wooster, Bertie (Fictitious character) -- Fiction; Jeeves (Fictitious character) -- Fiction; Single men -- Fiction; Valets -- Fiction; Pepper, Reggie (Fictitious character) -- Fiction